A meta-stochastic frontier analysis for energy efficiency of regions in Japan - Satoshi Honma; Jin-Li Hu (Journal of Economic Structures, 2018)
This paper measures the metafrontier total-factor energy efficiency (TFEE) of 47 regions in Japan for the period 1996-2008, using the stochastic frontier analysis (SFA). The two-step output-oriented SFA approach by Huang et al. (J Prod Anal 42:241-254, 2014) is followed but converted into a two-step input-oriented SFA approach. The metafrontier TFEE is defined as a product of the group TFEE and the technological gap ratio (TGR). The mean group TFEE is smaller than the mean TGR for both the groups, which shows that the energy inefficiency in Japanese regions with respect to the metafrontier comes from primarily operating inefficiency, rather technology gap. The mean metafrontier TFEE of the metropolitan areas is smaller than that of rural areas, implying that the former is energy inefficient than the latter. The mean TGR of the metropolitan areas is also smaller than that of rural areas, implying that many Japanese regions with major cities are far below the metafrontier and still have much room for energy savings.
Keywords: 330; Two-step input stochastic frontier analysis; Input metafrontier analysis; Energy efficiency